Economic Impacts of Intellectual Property-Conditioned Government Incentives - Prud'homme, Dan.; Song, Hefa.; SpringerLink (Online service) (Singapore : Springer Singapore (Imprint), 2016)
This book provides new insights into the economic impacts, strategic objectives and legal structures of an emerging branch of government incentives conditioned on meeting intellectual property-related requirements. Despite becoming more common in recent years, such incentives - ranging from patent fee subsidies and patent box tax deductions to inventor remuneration schemes - are still under researched. In-depth empirical studies from China and Europe of interest to scholars as well as policymakers and practitioners are presented. Readers benefit from the conceptual and practical insights as well as policy recommendations provided.
Keywords: Law and economics; Mass media -- Law and legislation; Economic policy